2014
DOI: 10.6023/a13111123
|View full text |Cite
|
Sign up to set email alerts
|

Construction of AgrC Proteoliposomes by Detergent-Mediated Method

Abstract: To respond appropriately to different environmental changes, bacteria have evolved two-component signal transduction systems (TCSTs), which are absent in mammals (including human beings). A typical TCST consisted of a sensor kinase (histidine kinase, HK) and a response regulator (RR). HK is capable of autophosphorylation in response to an environmental signal, while RR interacts with the phosphorylated HK. Membrane protein AgrC is a sensor kinase of a TCST from Staphylococcus aureus. Illumination of signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…From the size change of liposome and proteoliposome, it can be concluded that VDAC-1 had been inserted into the liposomes. Moreover, the size of VDAC-1 proteoliposome showed high agreement with the Agrc proteoliposome (MW: 47 kDa; size: 301 nm) constructed by Wang et al, 28 indicating a successful construction of VDAC-1 proteoliposome in this study.…”
Section: Characterization Of Vdac-1 Proteoliposomesupporting
confidence: 86%
“…From the size change of liposome and proteoliposome, it can be concluded that VDAC-1 had been inserted into the liposomes. Moreover, the size of VDAC-1 proteoliposome showed high agreement with the Agrc proteoliposome (MW: 47 kDa; size: 301 nm) constructed by Wang et al, 28 indicating a successful construction of VDAC-1 proteoliposome in this study.…”
Section: Characterization Of Vdac-1 Proteoliposomesupporting
confidence: 86%
“…As a platform for studying membrane proteins, liposomes provided an approximate hydrophobic environment that can maintain the functional activity of membrane proteins to the maximum extent (Rigaud & Lévy, 2003). Currently, there are methods to incorporate proteins into liposomes (Pool & Bolhuis, 2010;Wang, Quan, Xu, et al, 2014). The detergent-mediated method had more advantages than other methods.…”
Section: Effects Of Rhein and Aloeemodin On Transcriptional Regulatmentioning
confidence: 99%
“…In a previous study, an artificial cell membrane system with truncated AgrC (AgrC TM5‐6C ) was successfully constructed. This protein has two transmembrane segments, an extracellular loop, and a cytoplasmic domain and retains kinase activity after reconstruction (Wang, Quan, Liu, et al., ; Wang, Quan, Xu, et al., ). Furthermore, we established an efficient and rapid method for quantitative determination of the orientation of AgrC TM5‐6C in the artificial cell membrane system (Xiong et al., ).…”
Section: Introductionmentioning
confidence: 99%